(untitled) - Lowe, Lois V. (Hoboken, N.J., 2012)
Word 2010 is one of the core applications of Microsoft Office and if you're eager to get started using all it has to offer, this value-packed eLearning Kit is essential to your learning process. This complete Word 2010 course includes a full-color printed book and a Dummies interactive eLearning course on CD. You'll discover the basics of the Word interface, how to navigate it, how to get comfortable with the terminology, and how to use its many features. Detailed instructions walk you through real-world exercises and help to make learning easier!
Keywords: Microsoft Word,Microsoft Word (Computer software),Microsoft Word (phần mềm máy tính)